Selective Synthesis, Characterization and Kinetics Studies of poly(α-Methyl styrene) induced by Maghnite-Na+ Clay (Algerian MMT) - Moulkheir Ayat; Mohamed Belbachir; Abdelkader Rahmouni (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
A new and efficient catalyst of Na-Montmorillonite (Na+-MMT) was employed in this paper for α-methylstyrene (AMS) cationic polymerization. Maghnite clay, obtained from Tlemcen Algeria, was investigated to remove heavy metal ion from wastewater. “Maghnite-Na” is a Montmorillonite sheet silicate clay, exchanged with sodium as an efficient catalyst for cationic polymerization of many vinylic and heterocyclic monomers. The various techniques, including 1H-NMR, 13C-NMR, IR, DSC and Ubbelohde viscometer, were used to elucidate structural characteristics and thermal properties of the resulting polymers. The structure compositions of “MMT”, “H+-MMT” and “Na+-MMT” have been developed. It was found that the cationic polymerization of AMS is initiated by Na+-MMT at 0 °C in bulk and in solution. The influences of reaction temperature, solvent, weight ratio of initiator/monomer and reaction time on the yield of monomer and the molecular weight are investigated. The kinetics indicated that the polymerization rate is first order with respect to the monomer concentration. A possible mechanism of this cationic polymerization is discussed based on the results of the 1H-NMR Spectroscopic analysis of these model reactions. A cationic mechanism for the reaction was proposed. From the mechanism studies, it was showed that monomer was inserted into the growing chains.